FAKTOR-FAKTOR YANG MEMPENGARUHI EFEKTIFITAS IMPLEMENTASI DIKLAT DAN HASIL DIKLAT PADA BADAN PENGEMBANGAN SUMBER DAYA MANUSIA PROVINSI KALIMANTAN TIMUR TAHUN 2017 - Iwan Heriawan (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2018)
The background of this research is the training of one of the efforts to realize the resources of quality apparatus through leadership training, the success of training institute is projected, that is: can print professional ASN realize East Kalimantan forward 2018, improve the implementation of national / international standard apparatus training, lecturers' quantity (widya iswara), improving the facilities of sapras supporting the repetitive and technological learning process and realizing the competence of civil state apparatus for changes in leadership management. This research method is aimed to explain hypothesis of influence and relationship based on theory and explain and prove the truth of influence and relationship that is influence of budget, instructor, and sapras (individual and simultaneous) to implementation of training and training result at East Kalimantan Provincial Human Resource Development Board. Based on the essence of the problem and the results of data analysis research can be concluded that the budget allocation of APBD has a positive and significant impact on the effectiveness of the implementation of the training. In terms of the size of the budget affects the effectiveness of the implementation of the training, instructor competence has a positive and significant impact on the effectiveness of the implementation of the training, sapras conditions have a positive and significant impact on the effectiveness of the implementation of the training, budget allocation has a positive and significant impact on the results of training, have a positive and significant effect on the results of the training, sapras conditions have a positive and significant impact on the results of the training, the effectiveness of the implementation of education and training has a positive and significant impact on the results of the training, budget allocation of APBD, instructor competence, and sapras conditions simultaneously have influence which is positive and significant to the effectiveness of the implementation of the training, budget allocation of APBD, instructor competence, sapras conditions, and effectiveness of the implementation of the training simultaneously have a positive and significant influence t to the results of the training.Keywords: Effectiveness, Competence, Budget Allocation